Evaluation of an advisory committee as a model for patient engagement - Cynthia Kendell (The Beryl Institute, 2014)
Patient engagement (PE) is not well defined and little guidance is available to those attempting to employ PE in decision-making relevant to health system improvement. After completing a 2-year PE project, overseen by an Advisory Committee, our objectives were: 1) to evaluate how effectively the project team engaged the Advisory Committee, 2) to examine how Advisory Committee members perceived PE and their role in PE, and 3) to identify barriers and facilitators to PE in order to improve future efforts. Five members of the Advisory Committee completed semi-structured interviews post-project about their experiences. Thematic analysis identified four themes: the approach, participant contributions, participant understanding of PE, and barriers and facilitators to PE. The use of a committee approach was considered beneficial, providing an opportunity to discuss the project in depth, contributing to relationship building, and helping move the project forward. The social aspect of the committee approach was an important part of the engagement process. Participants felt they contributed primarily by participating in discussion, yet could not identify specific contributions they had made. All participants agreed that the experience was meaningful but not profound with regard to how it would impact their engagement, or their engagement of others, in the future. Although experiences were highly subjective, this study suggests that the act of participating in PE has meaning in and of itself to those involved, independent of the activities and/or outcomes of that participation, reflecting a broader public value that PE is an important component of transparent, accountable health systems.